Rare Case of Focal Organising Pneumonia With Extension to Interlobar Space and Adjacent Lobe Initially Suspected as Lung Cancer - Sachie Koike; Takayuki Shiina; Keiichiro Takasuna; Akane Kato; Koudai Komatsu; Toshitsugu Nakamura (Respirology Case Reports)
ABSTRACT Organising pneumonia is histopathologically characterised by inflammatory granulation tissue plugs within the lumen of the small airways, extending into the alveolar ducts and airways. Focal organising pneumonia is an organising pneumonia that presents as a solitary nodule or mass on computed tomography. This type of organising pneumonia is sometimes initially suspected to be lung cancer. We report a rare case of focal organising pneumonia that extended to the interlobar space and adjacent lobe and was initially suspected of lung cancer with interlobar pleural invasion. This case of focal organising pneumonia may have been induced by Fusobacterium nucleatum infection. This is the first report of a focal organising pneumonia extending to the interlobar space and adjacent lobe.